EVALUASI KETAHANAN 14 GENOTIPE CABAI TERHADAP INFEKSI CHIVMV (CHILLI VEINAL MOTTLE VIRUS) - Zahratul Millah (Jurnal Agroekoteknologi, 2009)
ABSTRACTOne of the major problem in chillipepper production was virus infection, with Chilli Veinal Mottle Virus (ChiVMV) as one of the most important viruses in Asia. Strategy to manage virus infection is not easy. The use of resistant varieties was considered as the best strategy to control viral disease. The research was undergone to find resistant genotypes of chillipepper that can be used as sources of ChiVMV resistance genes. This evaluation involve 14 genotypes from the collection of Genetic and Plant Breeding laboratory, Department of Agronomy and Horticultura. ChiVMV isolat Cikabayan was used for the source of inoculum. Based on the response from twice evaluation, it was known that PBC495, ICPN12#4, CCA321 and VC211a-3-1-1-1 genotypes were consistence in the response of resistance to ChiVMV infection. PBC495, VC211a-3-1-1-1 and CCA321 were identified as resistant genotypes and ICPN12#4 was identified as susceptible genotype.Key words: chillipepper, resistance, chilli veinal mottle virus